Komunikasi Beragama Dan Harmoni Sosial (Kasus Akulturasi Budaya Islam – Kristen Masyarakat Besitang, Kabupaten Langkat Sumatera Utara) - AG, Hamdani (Jurnal Komunikasi Islam, 2017)
Acculturation is the process of cultural and psychological changes as a result of the communication of two or more cultural groups in members of a particular culture. Acculturation allows the birth of a new cultural diversity that can be accepted by all members of multiethnic communities, not least the cultural heritage of certain ethnic, creativity or initiative outcomes and culture coming from the outside. Acculturation is able to knit religious communication and social harmony among multireligious society, based on mutual respect and respecting others. Because of acculturation integrate all cultural subcultures such as customs, traditions, language, art, values and norms, education and livelihood, except the matter of aqidah (faith) impossible to be acculturated. Community of Besitang district, Langkat, North Sumatra comprising Malays, Javanese, Acehnese and Minangkabau Muslim and Karo and Batak Christians have managed to reach the level of the most successful acculturation. Muslim and Christian leaders, as well Subdistrict leaders and harmony forum (FKUB) highly committed local creating a harmonious atmosphere and religious harmony in the community, through the cultural approach to all ethnic groups. This, proved able to create a safe atmosphere, peace, and harmony without social conflict in the middle of the multiethnic and multireligious society